(untitled) (American Journal of Islam and Society, 2023)
In 2019 Professor Ahmet Kuru published his acclaimed Islam, Authoritarianism, and Underdevelopment: A Global and Historical Comparison. I say ‘acclaimed’ not as an endorsement but merely to point to accolades it received, such as the jointly awarded and prestigious 2020 American Political Science Association’s Jervis-Schroeder Book Award. Moreover, it was keenly promoted by Kuru and publishers via a global book tour including Harvard, on top of receiving reviews in Foreign Affairs and numerous political science and history journals. More recently, its arguments featured in a widely reported op-ed penned by former UK Prime Minister Tony Blair in the wake of the Taliban reconquest of Afghanistan, where he characteristically decries ‘Islamism’ as “a first-order security threat to the west”.